1981
DOI: 10.1210/endo-109-5-1723
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Insulin Resistance in Vitro: Evidence for Both Receptor and Postreceptor Defects*

Abstract: Glucocorticoid excess in vivo has been shown to cause decreases in insulin sensitivity and insulin receptor binding in target tissues. It has not been previously possible to produce all of these changes in vitro because of limitations of the isolated rat adipocyte as an experimental model. We have studied the effects of glucocorticoid hormones on insulin binding and insulin action in differentiated mouse 3T3-L1 fatty fibroblasts, in an attempt to develop a complete in vitro model of the insulin resistance asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…Studies using blood cells, fibroblasts and adipocytes have shown that glucocorticoids decrease the insulin-stimulated rate of glucose transport and the binding of insulin to its receptors [5][6][7][8][9][10]. Although muscle is quantitatively most important for glucose disposal in response to insulin [11], there are very few reports on the effects of glucocorticoids on this tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using blood cells, fibroblasts and adipocytes have shown that glucocorticoids decrease the insulin-stimulated rate of glucose transport and the binding of insulin to its receptors [5][6][7][8][9][10]. Although muscle is quantitatively most important for glucose disposal in response to insulin [11], there are very few reports on the effects of glucocorticoids on this tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there usually exists an inverse relationship between insulin binding and fasting plasma insulin levels in hyperinsulinemic states ( 9 , which was not found to be the case in the present study where insulin binding increased despite fasting hyperinsulinemia. In human and animal studies, other glucocorticoids such as cortisone and dexamethasone have been shown to cause insulin resistance by interfering at both receptor and postreceptor steps (10,21). Insofar as insulin receptors on erythrocytes reflect the status of insulin receptors on major target tissues like muscle, liver, and fat, our results suggest that prednisone-induced insulin resistance results from postreceptor defects.…”
Section: Discussionmentioning
confidence: 65%
“…Animal and in vitro studies have led to conflicting results: the effects of glucocorticoids on insulin binding to its receptor were variable, depending on the type of glucocorticoid tested, the cellular model used and the duration of its exposure to steroid (7,10,21,23,31,32). The investigation of insulin binding after glucocorticoid administration to human subjects has also provided ambiguous results (3,11,15,29,38).…”
mentioning
confidence: 99%
“…In these differentiating 3T3-L1 cells dexamethasone has been already shown to elicit a/5'1 to ~'2 switch of ~-adrenergic receptor subtypes [25] and to mimic some aspects of insulin resistance including both receptor and postreceptor defects [26]. From our studies, it is probable that the appearance of ACTH receptors, evidenced in 3T3-LI adipocytes by Grunfeld et al [27], is linked to the presence of dexamethasone in the differentiation protocol used by these authors.…”
Section: Discussionmentioning
confidence: 99%